DEVELOPING INDEPENDENT LEARNING COMPETENCE IN FOREIGN LANGUAGE ACQUISITION THROUGH AN INTEGRATIVE APPROACH - Xudoyarova Dildora Najmidinovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article examines the role of an integrative approach in developing students’ independent learning competence in foreign language acquisition. The study analyzes how combining linguistic, cognitive, and interdisciplinary strategies promotes autonomous learning, critical thinking, and self-regulation. By implementing interactive methods, project-based tasks, and technology-enhanced learning, students engage in meaningful, self-directed activities that enhance language proficiency and learning motivation. The findings indicate that an integrative approach supports continuous skill development, fosters learner autonomy, and prepares students to adapt effectively to diverse academic and professional contexts.